General practitioner workforce sustainability to maximise effective and equitable patient care: findings from a realist review - Park, S; Owen-Boukra, E (Nuffield Department of Primary Care Health Sciences, University of Oxford, 2025)
UK and global primary care are in crisis with a shortage of General Practitioners (GPs) (1, 2). Recent strategies to address this have included attempts to reduce GP workload, such as the introduction of technology and additional healthcare professional roles (3). However, it remains unclear whether these strategies are effective at sustaining the GP workforce. Previous research about the GP workforce has tended to focus on individual factors (e.g. recruitment and retention) (1). This review takes a broader view, to understand how the nature of GP work, social interactions and related organisational and system-level factors influence GP workforce sustainability. Throughout this review, we included a strong focus on approaches which facilitate GPs to provide effective and equitable patient care. We aimed to look ‘under the bonnet’ of GP work to explore not only why people might leave, but also understand the ‘glue’ and ‘joy’ which enable GPs to flourish and thrive (4, 5).